Fostering Resilient Health Systems in India: Providing Care for PLHIV Under the Shadow of COVID-19 - Parikh, Neha; Chaudhuri, Angela; Syam, Syama B.; Singh, Pratishtha (Frontiers in Public Health, 2022)
Introduction- The novel coronavirus or COVID-19 has resulted in major human casualties, and extreme socio-economic crises causing catastrophic disturbances to health systems and communities alike. This study qualitatively explores the challenges experienced by healthcare providers while providing services to people living with HIV (PLHIV) during the pandemic outbreak and subsequent lockdown in India. The paper also explores strategies developed and adopted to provide continued care for PLHIV. Methods- Using an empirical phenomenological approach, qualitative in-depth telephonic interviews were conducted with 19 HIV care providers from 5 states in India. The recorded interviews were transcribed and analyzed using inductive thematic analysis with the help of Dedoose software. Results- From the analysis of participants’ narratives, three main themes emerged: (1) Challenges of working during a pandemic; (2) Remodeling care delivery to ensure continuity of services; (3) Resilience. Discussion- Our findings highlight the challenges that providers faced, despite which, adaptive efforts were made to continue providing quality care for PLHIV through ingenious and innovative strategies. To foster resilient health systems, health workers are the primary stakeholders. We recommend formal social protection, comprehensive primary healthcare support, and sufficient capacity building for health workers for their self-care and pandemic preparedness.